Effect of Growth Hormone on Glycogenesis in Rat Cerebral Cortical Slices. - VISWESWARAN, P.; KUMAR, BINOD; S.S. AZAD, V.; BRAHAMCHARI, A.K.; SINGH, S.P. (Asian Journal of Chemistry, 2010)
Incubation of cerebral cortical slices of growth hormone treated diabetic and normal rats with U–C14 glucose showed a two-fold increase in glycogenesis in dialetic rats. Glucose-6-phosphatase activity was lowered while the activities of phosphoglucomutase and phosphorylase were elevated in the cerebral cortex of diabetic rats treated with growth hormone. However, glycogen synthetase activity was slightly depressed.